Elements of Kareem national costumes in contemporary clothing - Ģibiete, Daina (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2012)
Research idea – on the basis of the folklore research materials to promote development of ethnographic style and its inclusion in Latvian clothing culture. Aim of the research: to study Kurzeme folk costumes from different perspectives and based on insights from the research to create a set of dress variants with ethnographic elements, colour combinations/compositions, interesting elements/components of clothing and today’s needs. It could be one way of promoting the the sense of belonging to Latvians. Methods: cultural-historical material research, ancient and Kurzeme region folk costume analysis, choice and selection of interesting elements, modern dressing style analysis, and costume design creation, practical work. Result: creation of one’s own design style, based on ethnographic-style options.